A Comparative Study on Financial Performance of Selected Public (Indian Bank) and Private (Hdfc Bank) Sector Banks in India - M. SUBRAMANYIAM REDDY, Dr. N. RAJENDHIRAN (International Journal of Advanced Science and Technology, 2020)
In India, The public sector together with private sector banks are very significant role in economic development in India. Usually, banks has involved in accepting deposits from the people (public) at a lower rate and issuing loans at higher rate and thereby making profit on interest margin. This paper aimed to analyze and differentiate the financial performance of selected public and private sector banks in India during from 2015 to 2019. The study period covers the five years of selected public (i.e. Indian Bank) along with private (i.e. HDFC Bank) sector banks. The study based on secondary source of data collected from their official sites and annual reports and the data analyzing through financial ratio and statistical tools such as Mean, Standard Deviation, Co- efficient of variance and F-Test (ANOVA) with help of SPSS. We analyzed the financial strength and weakness of the selected public along with private sector banks. In this paper, we ascertain that the private sector banks are best utilization of the accessible resources such as deposits, advances, assets, along with investments and it was also practical in the study that public sector banks have not utilized of their available resources properly. Therefore it has needed for the public sector banks to play more awareness on improving their efficiency and productivity of employee training, incentive and proper management